Inorganic-organic hybrid photochromic materials - Wang, Ming-Sheng; Xu, Gang; Zhang, Zhang-Jing; Guo, Guo-Cong (Chemical communications (Cambridge, England), 2010)
The distinct synergetic characteristics between each component in inorganic-organic hybrids offer various possibilities to obtain new "smart", high performing materials. Growing interest in this field has largely expanded the content of photochromic materials for the purpose of improving existing photochromic materials, fabricating photoresponsive devices, and exploring new families of photochromic materials. In this feature article, we give a brief review of photochromic hybrids of metal halides, metal cyanides, polyoxometalates, and metal chalcogenides as well as photochromic metal-organic complexes.